Governors, Grants, and Elections : Fiscal Federalism in the American States - Nicholson-Crotty, Sean (Book collections on Project MUSE., 2015)
"Each year, states receive hundreds of billions of dollars in grants-in-aid from the federal government. Gubernatorial success is often contingent upon the pursuit and allocation of these grants. In Governors, Grants, and Elections, Sean Nicholson-Crotty reveals the truth about how U.S. governors strategically utilize these funds. Far from spending federal money in apolitical ways, they usually pursue their own policy interests in the hopes of maximizing their or their party's electoral success. Nicholson-Crotty analyzes three decades of data on the receipt and expenditure of grants in all fifty states. He also draws compelling evidence from governors' public speeches and interviews with state officials. Ultimately, he demonstrates that incumbent governors' use of grants to deliver policies desired by core constituents--along with their opportunistic funding of public and private goods that appeal to noncore median voters--enables them to increase approval, legislative success, and, ultimately, vote share for themselves or their parties. The inaugural book in the Johns Hopkins Studies in American Public Policy and Management series, Governors, Grants, and Elections is a significant and accessible work of public policy scholarship that sits at the nexus of multiple fields within political science."--Provided by publisher.